Analisis Yuridis terhadap Studi Putusan Pengadilan Agama Kraksaan Nomor: 1487/PDT.G/2019/PA. KRS - Khosnol Khotimah; Yuniar Kusuma Wardani; Muhammad Amin Warsito; Melita Badriyatus Zuhroh; Abdul Rouf; Syamsuri Syamsuri (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Absract: A common treasure isa treasure acquired during a marriage, apart from gifts and inheritances. The idea is that both the possessions are acquired through the business of husband and wife. The Shared division of property resulting from the law after a divorce both husband and wife would be concerned about the property of a